Clinical insights into tooth extraction via torsion method: a biomechanical analysis of the tooth-periodontal ligament complex - Xing, Jiawei; Zhang, Guangzeng; Sun, Mingliang; Pan, Hao; Zhang, Congdi; Liu, Yao; Li, Kehan; He, Ze; Zhang, Kailiang; Wang, Jizeng; Luo, En; Zhang, Baoping (Frontiers in Bioengineering and Biotechnology, 2024)
Traditionally, extracting single, flat-or curved-rooted teeth through twisting is unfeasible. However, our clinical practice suggests that such teeth can be extracted efficiently through moderate twisting in a minimally invasive manner. Given the lack of studies on biomechanics of the tooth-periodontal ligament (PDL) complex during torsion, which has further constrained its application, we assessed the feasibility of the torsion method for extracting single-rooted teeth and evaluated its minimally invasive potential. Using three-dimensional finite element analysis, we examined the stress distribution of the tooth and PDL during torsion. Then, we examined changes in the optimal torsion angle (OTA) and stress distribution across various anatomical scenarios.During torsion loading, stress concentration was primarily observed on the sing-rooted tooth surface near the alveolar crest, whereas molars at the root furcation. The OTA was found to increase under conditions such as narrowing of root width, decrease in the root apical curvature, change from type I to IV bone, alveolar bone loss, and shortening of root length. Moreover, the clinically validated model demonstrated that 74% of outcomes fell within the standard OTA range.In conclusion, the decrease in PDL area necessitated a larger angle for complete PDL tearing.Single-rooted teeth with root width-to-thickness ratios of ≥0.42 and apical curvatures of ≤30°a re suitable for extraction using the torsion method. This study confirms the feasibility of the torsion method for minimally invasive tooth extraction and expands its indications, laying the theoretical foundation and essential insights for its clinical application.